Factors responsible for the higher transcriptional activity of extracts of adenovirus-infected cells fractionate with the TATA box transcription factor. - Leong, K (1988)
Extracts of adenovirus-infected HeLa cells have 5- to 10-fold-higher activity for transcription from the major late promoter in vitro than do extracts of mock-infected or E1A mutant-infected cells (K. Leong and A. J. Berk, Proc. Natl. Acad. Sci. USA 83:5844-5848, 1986). In this study, we analyzed extracts from mock-infected cells and from cells infected with an E1A mutant, pm975, which expresses principally the large E1A protein responsible for the stimulation of transcription. These extracts were fractionated by phosphocellulose chromatography, a procedure which separates factors required for transcription from this promoter (J. D. Dignam, B. S. Shastry, and R. G. Roeder, Methods Enzymol. 101:582-589, 1983), allowing the quantitative assay of individual factors (M. Samuels, A. Fire, and P. A. Sharp, J. Biol. Chem. 257:14419-14427, 1982). Fractions eluted with 0.04, 0.35, and 0.6 M KCl, which contained RNA polymerase II, the upstream factor MLTF, and three general polymerase II transcription factors, had similar activities when prepared from virus-infected or from mock-infected cells. The sequence-specific DNA-binding activity of MLTF was also similar in the virus-infected- and mock-infected-cell extracts. In contrast, the 1.0 M KCl fraction prepared from virus-infected cells consistently exhibited activity severalfold higher than that of the equivalent fraction prepared in parallel from mock-infected cells. E1A protein eluted principally (greater than 80%) in the 0.35 M KCl fraction. Results of others (M. Sawadogo and R. G. Roeder, Cell 43:165-175, 1985) have shown that the 1.0 M KCl fraction, containing 2 to 5% of the unfractionated protein extract, contains a factor which binds specifically to the major late promoter TATA box. These results, together with a recent genetic analysis of the E1B promoter which demonstrated that the TATA box was required for its efficient transcriptional activation (transactivation) by E1A (L. Wu, D. S. E. Rosser, M. Schmidt, and A. J. Berk, Nature (London) 326:512-515, 1987), are consistent with the model that E1A protein indirectly activates the TATA box transcription factor. Consistent with this model was the finding that mutants of the major late promoter containing only the TATA box and cap site region were transcribed at higher rates with extracts from virus-infected cells than with extracts from mock-infected cells. Other models consistent with the results are also discussed.